2020
DOI: 10.1101/2020.07.19.211250
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Optogenetic activation of spinal microglia triggers chronic pain in mice

Abstract: Spinal microglia are highly responsive to peripheral nerve injury and are known to be a key player in neuropathic pain. However, there has not been any direct evidence showing selective microglial activation in vivo is sufficient to induce chronic pain. Here we used optogenetic approaches in microglia to address this question employing CX3CR1creER/+: R26LSL-ReaChR/+ transgenic mice, in which red-activated channelrhodopsin (ReaChR) is inducibly and specifically expressed in microglia. We found that activation o… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 74 publications
(93 reference statements)
0
2
0
Order By: Relevance
“…Progress in the RNA sequencing (RNA-seq) techniques demonstrated a multiple spectrum of reactive microglial subtypes in the diseased conditions [ 61 , 62 ]. Recent RNAseq studies showed that pro-inflammatory cytokine and immunomodulatory drivers: complements, FcɣRs, and INFs are the important upstream mediators of nerve injury-induced gene regulation in reactive microglia in abnormal maladaptive state over long periods of pain hypersensitivity [ 16 ]. It was well documented that microglia are critical in developing neuropathic pain especially in the initiation, during which, the release of BDNF, cytokines such as TNF-α and IL-1β are essential for the establishment of pain hypersensitivities [ 63 , 64 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Progress in the RNA sequencing (RNA-seq) techniques demonstrated a multiple spectrum of reactive microglial subtypes in the diseased conditions [ 61 , 62 ]. Recent RNAseq studies showed that pro-inflammatory cytokine and immunomodulatory drivers: complements, FcɣRs, and INFs are the important upstream mediators of nerve injury-induced gene regulation in reactive microglia in abnormal maladaptive state over long periods of pain hypersensitivity [ 16 ]. It was well documented that microglia are critical in developing neuropathic pain especially in the initiation, during which, the release of BDNF, cytokines such as TNF-α and IL-1β are essential for the establishment of pain hypersensitivities [ 63 , 64 ].…”
Section: Discussionmentioning
confidence: 99%
“…Using microglia ablation and chemogenetic approaches, studies have shown that microglial proliferation and neuroinflammation in response to nerve injury are key players in the induction of pain hypersensitivities [ 11 15 ]. Interestingly, optogenetic activation of spinal microglia is able to directly trigger “microgliogenic pain” [ 16 ]. The most well-known molecular mechanism involves microglial P2X4 receptor (P2X4R), which induces BNDF release and dis-inhibition in spinal lamina I neurons leading to pain hyperalgesia [ 17 20 ].…”
Section: Introductionmentioning
confidence: 99%